Comparative Analysis of Safety Performance Indicators Based on Inductive Loop Detector Data - Mamdoohi, Amir Reza; Fallah Zavareh, Mohsen; Hydén, Christer; Nordfjærn, Trond (Promet - Traffic&Transportation, 2014)
Conflicts in traffic stream have been detected by different safety performance indicators. This study aims to empirically investigate the differences between different indicators in detecting rear-end conflicts and assessing the risk in an uninterrupted flow. Micro-level data of a 24-hr traffic stream (including 6,657 vehicles) were captured using inductive loop detectors installed on a rural freeway section. Different indicators (Time Headway (H), Time to Collision (TTC), Proportion of Stopping Distance (PSD), Deceleration Rate to Avoid Collision (DRAC) and Stopping Distance Index (SDI)) were used to measure each car following event in a bivalent state (safe/unsafe). Unsafe events associated with each indicator were detected and common unsafe events characterized by different indicators were identified. Temporal distributions of rear-end collision risks associated with each indicator at 15-min intervals were also compared. Finally, the 15-min risk values based on different indicators were categorized and compared across three levels (Low, Medium and High). Data mining and statistical techniques showed that while SDI is the single most conservative indicator, DRAC and TTC detect a few risky events but very equal ones. In almost all conflicts associated with TTC, headway is still lower than the critical threshold. However, there exist considerable risky events based on headway which are still safe according to TTC. Comparison of PSD and TTC also declares that almost all conflicts associated with TTC are also risky according to PSD.